KEPEMIMPINAN CAMAT DALAM MENINGKATKAN KEDISIPLINAN APARATUR PEMERINTAH DI KECAMATAN TUMPAAN KABUPATEN MINAHASA SELATAN - Jerry H. H. Masinambow; Joyce J. Rares; Fanley ., Pangemanan (Sam Ratulangi University, 2021)
This study aims to determine how camat leadership is in improving the discipline of government officials in Tumpaan District, Minahasa Regency. The research method used is descriptive qualitative by using the interview guide technique, observation, and documentation. The results showed that the leadership of the subdistrict head on improving the discipline of work of government officials in the Tumpaan District has not been carried out optimally, where there are still has a fault or disciplinary violations committed by officials regarding working hours as a form of regulation and there are delays in completing tasks. Actions given by the leadership to subordinates who do not comply with the applicable regulations that actions taken by superiors who violate discipline are given based on the level of fault committed.